INTEGRASI EDUKASI LINGKUNGAN DAN KEARIFAN LOKAL DALAM GERAKAN BERSIH DESA HILIAMAETALUO, KABUPATEN NIAS SELATAN - Agustin Sukses Dakhi (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to enhance environmental awareness through the integration of environmental education and local wisdom in Hiliamaetaluo Village, South Nias Regency. The village possesses significant socio-cultural potential, including local wisdom values such as mutual cooperation (gotong-royong), prohibitions against dumping waste into rivers, and respect for nature inherited from ancestors. However, environmental management practices still face challenges, including habitual littering, limited supporting facilities, and a lack of awareness among younger generations regarding traditional values. The program was implemented through several stages: identification of environmental issues, environmental education workshops based on local wisdom, village clean-up activities, and participatory community evaluation. This method combines participatory, educational, and cultural approaches, making it easier for the community to understand the importance of environmental conservation while instilling cultural values. The results indicate increased community participation, initial behavioral changes in waste sorting and management, public space greening, and the formation of collective awareness to protect the environment. Furthermore, the program strengthened the community’s sense of ownership, positioning local wisdom values as ethical and practical foundations for environmental management. This community service demonstrates that the integration of environmental education and local wisdom can serve as an effective strategy for sustainable village-level development while reinforcing cultural identity and social solidarity. This model has the potential to be replicated in other villages with similar cultural contexts.